The complete mitochondria genome of Parasarcophaga albiceps (Diptera: Sarcophagidae). (1st November 2016) - Liao, Huidan; Yang, Xiang; Li, Zhilong; Ding, Yanjun; Guo, Yadong
Abstract: Parasarcophaga albiceps is one of the forensically important fly species which belongs to the family Sarcophagidae. In this study, we report the complete mitochondrial genome of P. albiceps to provide a supplemental data for species identification. The 14 935 bp-long mitogenome is composed of 13 protein-encoding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a non-coding AT-rich region. The permutation of the genes is in conformity with that observed in the ancestral arthropod. The overall base compositions of A, G, C and T are 39.24%, 9.70%, 14.44%, and 36.62%, respectively. Phylogenetic analysis shows the composition of the P. albiceps mitochondrial genome, which is very similar to that of another eight species of Sarcophagidae. The monophyletic branches of the phylogenetic tree reveal that complete mitochondrial genome is suitable for discrimination between these species, providing high support for separation on congeneric species. Therefore, the molecular method applied to the sarcophagid species identification is feasible. The complete mitochondrial genome of P. albiceps is supposed to make contributions to enriching the dipteran mitochondrial genomes and provide a potential tool for species identification.